Protective Effects and Network Analysis of Ginsenoside Rb1 Against Cerebral Ischemia Injury: A Pharmacological Review - Wang, Kaili; Wang, Xin; Yang, Tao; Wu, Yumei; Yang, Dongsheng; Chen, Shuaishuai; Zhao, Xuanyin; Xiao, Tianbao (Frontiers in Pharmacology, 2021)
Ischaemic stroke is a leading cause of death and disability worldwide. Currently, only a limited number of drugs are available for treating ischaemic stroke. Hence, studies aiming to explore and develop other potential strategies and agents for preventing and treating ischaemic stroke are urgently needed. Ginseng Rb1 (GRb1), a saponin from natural active ingredients derived from traditional Chinese medicine (TMC), exerts neuroprotective effects on the central nervous system (CNS). We conducted this review to explore and summarize the protective effects and mechanisms of GRb1 on cerebral ischaemic injury, providing a valuable reference and insights for developing new agents to treat ischaemic stroke. Our summarized results indicate that GRb1 exerts significant neuroprotective effects on cerebral ischaemic injury both in vivo and in vitro, and these network actions and underlying mechanisms are mediated by antioxidant, anti-inflammatory and antiapoptotic activities, and involve the inhibition of excitotoxicity and Ca2+ influx, preservation of blood-brain barrier (BBB) integrity and maintenance of energy metabolism. These findings indicate the potential of GRb1 as candidate drug for treating ischemic stroke. Further studies, in particular clinical trials, will be important to confirm its therapeutic value in clinical setting.